Leadership Tasks in Early Childhood Education in Finland, Japan, and Singapore. Issue 3 (2nd July 2016) - Hujala, Eeva; Eskelinen, Mervi; Keskinen, Soili; Chen, Christine; Inoue, Chika; Matsumoto, Mariko; Kawase, Masahiro
ABSTRACT: Leadership research in early childhood education and care (ECEC) is a relatively new undertaking. It combines leadership concepts from school research as well as from business. There are common aspects in the leadership profession, but the context and the mission define the content of leadership tasks and responsibilities. Data in this cross-cultural study were collected in Finland, Japan, and Singapore from 2012 to 2014. Questionnaires were used as the data collection method and content analysis as the method to explore how leadership tasks define leadership in the different countries. The project included 100 participants in each country. Analysis in this article focuses on leadership tasks in ECEC settings in Finland, Japan, and Singapore. The study revealed that the tasks of ECEC leaders in all three countries are similar—the two most important leadership tasks are pedagogical leadership and human resource management—though implementation of tasks varied based on cultural context. In practice, leaders in Finland spend most of their time in line with the two issues considered most important, leaders in Japan spend their time on service and human resource management, and leaders in Singapore spend their time on pedagogical leadership and service management.